Capacity utilization, inflation, and monetary policy: the Dumenil and Levy Marco Model and the new Keynesian consensus - Lavoie, Marc; Kriesler, Peter (2007)
The article considers the adjustment toward long-run equilibrium within the Dumenil and Levy macro model, with modifications. Findings show that long-run convergence to fully adjusted positions with normal utilization is not achieved when a more realistic reaction function is proposed. Classical equilibrium occurs when a vertical Phillips curve is substituted, but the model is isomorphic to the "new consensus" model and to features of "new" endogenous growth theory. - Reproduced.
Keywords: Inflation; Monetary policy